1985
DOI: 10.1097/00003446-198505000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Human Auditory Steady State Evoked Potentials during Sleep

Abstract: The human auditory steady state evoked potentials were recorded during all-night sleep in 10 subjects. The effects of stimulus rate and intensity on these potentials were measured using on-line Fourier analysis. The amplitude of the response was greatest at stimulus rates of 30 to 50/sec. Although the response amplitude was lower during sleep, the rate at which the amplitude was greatest did not change between sleep and wakefulness. As the intensity was increased above threshold, the amplitude of the response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(49 citation statements)
references
References 2 publications
5
42
0
2
Order By: Relevance
“…Spontaneously occurring gamma oscillations vary according to behavioral state, being higher during wakefulness than during NREM sleep (12) and reduced in anesthesia (13). Similarly, the ASSR power is reduced by about 50% during sleep (28) and is abolished by deep anesthesia (42). Although other parts of the ARAS, such as the thalamus (3), likely are important, our results suggest that BF PV neurons are involved in state-dependent control of GBO.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Spontaneously occurring gamma oscillations vary according to behavioral state, being higher during wakefulness than during NREM sleep (12) and reduced in anesthesia (13). Similarly, the ASSR power is reduced by about 50% during sleep (28) and is abolished by deep anesthesia (42). Although other parts of the ARAS, such as the thalamus (3), likely are important, our results suggest that BF PV neurons are involved in state-dependent control of GBO.…”
Section: Discussionmentioning
confidence: 69%
“…However, this hypothesis has not been tested directly. Thus, here we tested the effect of selective excitation of BF PV neurons on the cortical EEG and the effect of selective inhibition on the 40-Hz auditory steady-state response (ASSR), a test of the ability of the cortex to generate GBO (26) widely used in clinical studies of anesthesia (27), hearing loss (28), and schizophrenia (5,29).…”
Section: Significancementioning
confidence: 99%
“…State of arousal may have influenced our results since infants were studied while asleep and adults were studied awake. The effect of arousal is seen probably on the amplitude of the middle latency components evoked at or near threshold (Linden et al 1985) and not at suprathreshold (Picton et al 1974). Since the intensity used in the present study was suprathreshold (40 dB above detection of wave V of the ABR) this is not considered to be a significant influence on our results.…”
Section: Discussionmentioning
confidence: 69%
“…Sleep and sedation have considerable effects on the physiological activity of the higher centers of the brain. Studies [Aoyagi et al, 1994a;Cohen et al, 1991;Dobie and Wilson, 1998;Galambos et al, 1981;Jerger et al, 1986;Linden et al, 1985;Plourde et al, 1991;Rees et al, 1986] have demonstrated that the 40-Hz ASSR response amplitude decreased during sleep and sedation. Plourde et al [1991] showed that 40-Hz ASSR response amplitudes were decreased to between one third to one half in sleeping humans, and a greater decrease was identified under conditions of general anesthesia.…”
Section: Origins Of the Auditory Steady-state Responsesmentioning
confidence: 99%